Effect of air temperature non-uniformity on water–air heat exchanger thermal performance – Toward innovative control approach for energy consumption reduction. (1st July 2016) - Ramadan, M.; Khaled, M.; El Hage, H.; Harambat, F.; Peerhossaini, H.
Graphical abstract: Highlights: Air temperature distribution affects air–water heat exchanger thermal performance. This effect is modeled using an in-house computational code. Non-uniformity in air temperature can increase or decrease the thermal performance by up to 5%. A new control approach is proposed to optimize the thermal performance. For a vehicle running 3 h, the new control approach reduces the fuel consumption by up to 1.34 L. Abstract: Parametric numerical analysis that explores the relation between the non-uniformity of air temperature distribution upstream of a heat exchanger and its thermal performance is performed. The obtained numerical results are employed toward the optimization of water–air heat exchanger thermal performance. Furthermore, the numerical results lay out the foundation to develop an innovative control approach for monitoring the airflow upstream of a cross-flow water–air heat exchanger that lead to the optimization of its thermal performance and energy consumption. Consequently, an in-house computational code is established to evaluate the aforementioned thermal performance based on known parameters; namely, distribution of upstream velocity and temperature of an air–liquid heat exchanger, the flow rate of heat exchanger liquid, in addition to the inlet liquid temperature. It was observed that non-uniformities in air temperature can, depending on the configuration, increase or decrease the thermal performance of a heat exchanger up to 5%. Additionally, controlling air temperature non-uniformities, the fuel consumption and carbon dioxide emission can be reduced by up to 0.97 kg (1.34 L) and 3.17 kg respectively for a vehicle running three hours per day.